2017
DOI: 10.1016/j.bbmt.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Fresh or Cryopreserved CD34 + -Selected Mobilized Peripheral Blood Stem and Progenitor Cells for the Treatment of Poor Graft Function after Allogeneic Hematopoietic Cell Transplantation

Abstract: CD34+-selected stem cell boost (SCB) without conditioning have recently been utilized for poor graft function (PGF) after allogeneic hematopoietic stem cell transplantation (allo-HSCT) with promising results. Unfortunately, many patients have been unable to receive the boost infusion as their donors were unwilling or unable to undergo an additional stem cell collection. Therefore, we conducted this study utilizing either fresh or cryopreserved peripheral blood stem cell products to create CD34+-selected boost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 22 publications
2
34
0
3
Order By: Relevance
“…No apparent difference in time to platelet (PLT) recovery (10 studies reporting median days to PLT count of >20 × 10 9 /L; five studies reporting median days to PLT count of >50 × 10 9 /L) or neutrophil engraftment (18 studies reporting median days to neutrophil count of >0.5 × 10 9 /L) was reported in any of the studies in comparison to controls (Table ). Moreover, no apparent difference in CD34+ cells infused (eight studies) was reported for patients receiving cryopreserved products compared to controls receiving fresh products (Table ). The yield of CD34+ cells available after thawing was 31% to 100% (data reported in eight studies).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No apparent difference in time to platelet (PLT) recovery (10 studies reporting median days to PLT count of >20 × 10 9 /L; five studies reporting median days to PLT count of >50 × 10 9 /L) or neutrophil engraftment (18 studies reporting median days to neutrophil count of >0.5 × 10 9 /L) was reported in any of the studies in comparison to controls (Table ). Moreover, no apparent difference in CD34+ cells infused (eight studies) was reported for patients receiving cryopreserved products compared to controls receiving fresh products (Table ). The yield of CD34+ cells available after thawing was 31% to 100% (data reported in eight studies).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, no apparent difference in CD34+ cells infused (eight studies) was reported for patients receiving cryopreserved products compared to controls receiving fresh products (Table ). The yield of CD34+ cells available after thawing was 31% to 100% (data reported in eight studies).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In prior studies, we and others have found that the CliniMACS Plus immunomagnetic selection method has shown superior CP and VCR compared with other technologies, particularly with regard to CD34+ cell selection from mobilized peripheral blood [5,11]. Since then, this technique has been successfully applied to CD34+ cell selections on bone marrow collections and umbilical cord blood, as well as on cryopreserved and thawed cells [12][13][14][15]. Further, other cell subtypes, including monocytes, NK cells and T-lymphocytes selected on the instrument have also been utilized in early phase clinical studies [8,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%